FREE SEX BEHAVIORAL FACTORS BASED ON THE HEALTH BELIEF MODEL: A STUDY IN TEENAGERS IN MUNA, INDONESIA - Tasnim Tasnim (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2019)
Background: Free sex behavior in Indonesian teen has vastly improved. Free sex issues is the concern for all. The aim of this research was to determine the factors of free sex behavioral based on the health belief model. Methods:This research was a cross sectional study. The population were 304 students and sample of 75 respondents, the sampling using simple random sampling technique. Results: The results showed that there is correlation between vulnerability/seriousness perception to free sex behavior, with Chi Square 9.182 (? = 0350). There is a correlation between the level of threat perception to free sex behavior with Chi Square 14.815 (? = 0.444). There is a correlation between religiosity to free sex behavior with Chi Square 23.628 (? = 0561). There is a relationship between the gender to free sex behavior with Chi Square 16,000 (? = 0462). There is a correlation between social media to free sex behavior with Chi Square 25,000 (? = 0.577). Conclusion: Factors affecting free sex behavior are perception of the level of vulnerability / seriousness and threat of disease due to sex, religiosity, gender and social media. We are expected to SMAN I Pasir Putih to be able in using this research as information and consideration in developing the knowledge of adolescents about the dangers of free sex behavior.